A longitudinal communication approach in advanced lung cancer: a qualitative study of patients’, relatives’ and staff's perspectives - Villalobos Bollen, Matthias Americo; Coulibaly, Kadiatou; Krug, Katja; Kamradt, Martina; Wensing, Michel; Siegle, Anja; Kuon, Jonas; Eschbach, Corinna; Winkler, Eva C.; Szecsenyi, Joachim; Thomas, Michael (European journal of cancer care, 2018)
Communication and the care of patients with advanced cancer are a dynamic, interactive and challenging process, often characterised in every day practice by discontinuity and lack of coordination. The objective of this study was to explore the patients’ and family-caregivers’ needs and preferences regarding communication, quality of life and care over the trajectory of disease. The second aim was to assess health professionals’ views on a longitudinally structured, forward-thinking communication approach based on defined milestones. A qualitative approach was chosen incorporating semi-structured interviews with nine patients with metastatic lung cancer and nine relatives, and focus groups with 15 healthcare providers from different professions involved in the care of these patients. Patients and relatives described a situation of shock and coping deficits with moments of insufficient communication and lack of continuity in care. Healthcare providers reported the strong need for improvement in communication within the team and between patients and professionals and welcomed the implementation of a longitudinal communication approach. Requirements for the implementation of a longitudinal communication approach include specific communication training with focus on the process that patients and relatives are involved in. Team-building measures and the necessary flexibility to respect individuality in life should be incorporated.